2012
DOI: 10.1126/science.1219351
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a 16-nm Cage Designed by Using Protein Oligomers

Abstract: Designing protein molecules that will assemble into various kinds of ordered materials represents an important challenge in nanotechnology. We report the crystal structure of a 12-subunit protein cage that self-assembles by design to form a tetrahedral structure roughly 16 nanometers in diameter. The strategy of fusing together oligomeric protein domains can be generalized to produce other kinds of cages or extended materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
263
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(273 citation statements)
references
References 16 publications
1
263
0
4
Order By: Relevance
“…Control SuPrA protomers containing entirely Ceru+32, entirely GFP-17, or an octamer of Ceru+32 juxtaposed with an octamer of GFP-17 were unstable at all NaCl concentrations, consistent with the experimental observations ( Supplementary Fig. 12, 13) Finer-grained structural modeling (i.e., of hydrophobic effects and counterion release) must await specific structural and physical details that should become manifest with further imaging (i.e., cryo-EM) experiments that better determine the precise symmetric arrangement of monomers.While previous studies have shown that it is possible to design synthetic protein oligomers either by modifying extant structures [13][14][15][16] or de novo, [8][9][10][11][12] we now show that it may be possible to induce the formation of novel quaternary structures through the simple expedient of supercharging. In so doing, we demonstrate that precise molecular configurations can be obtained by focusing on the driving forces for assembly (charge:charge interactions) rather than the details of the interface.…”
mentioning
confidence: 99%
“…Control SuPrA protomers containing entirely Ceru+32, entirely GFP-17, or an octamer of Ceru+32 juxtaposed with an octamer of GFP-17 were unstable at all NaCl concentrations, consistent with the experimental observations ( Supplementary Fig. 12, 13) Finer-grained structural modeling (i.e., of hydrophobic effects and counterion release) must await specific structural and physical details that should become manifest with further imaging (i.e., cryo-EM) experiments that better determine the precise symmetric arrangement of monomers.While previous studies have shown that it is possible to design synthetic protein oligomers either by modifying extant structures [13][14][15][16] or de novo, [8][9][10][11][12] we now show that it may be possible to induce the formation of novel quaternary structures through the simple expedient of supercharging. In so doing, we demonstrate that precise molecular configurations can be obtained by focusing on the driving forces for assembly (charge:charge interactions) rather than the details of the interface.…”
mentioning
confidence: 99%
“…Algumas descrições eram mais precisas e relatavam estudos sobre nanotubos de carbono (Baughman, 2000;Service, 2000;Dresselhaus, 2001;Gogotsi, Simon, 2011), nanotubos de DNA (Yin et al, 2008), nanopartículas metálicas (Buriak, 2004;Service, 2005a;Schliehe et al, 2010), nanocápsulas cristalinas (Buriak, 2004), por exemplo; outras abordavam um panorama mais amplo sobre a possibilidade de produzir novos materiais a partir da manipulação nos níveis atômico e molecular (Besenbacher, Norskov, 2000;Service, 2002;Parak, 2011, Lai et al, 2012.…”
Section: Figura 6 áReas De Aplicação Nanotecnológicaunclassified
“…Os mesmos relatos descrevem a felicidade dos pesquisadores (Proffitt, 2004), sua empolgação (Cho, 2006;Aldaye et al, 2008, Shalaev, 2008Brongersma, Shalaev, 2010;Boltasseva, Atwater, 2011;Hamburg, 2012) e seu fascínio (Dzenis, 2004;Shalaev, 2008;Parak, 2011) pela performance (Osborne, Clery, 2004;Ruiz et al, 2008;Brongersma, Shalaev, 2010), pela beleza (Murphy, 2002;Cho, 2006;Schliehe et al, 2010;Service, 2011) e perfeição (Forró, 2000;Siegel, 2004;Ruiz et al, 2008;Lai et al, 2012) de seus resultados. A descrição da nanotecnologia desta forma entusiasta não é sem propósito e reforça a capacidade que o discurso científico tem de revelar ou ocultar algum aspecto de sua atividade para o público em geral (Latour, 2000).…”
Section: A Escolha Dos Termos No Discurso Científicounclassified
See 1 more Smart Citation
“…We now have experimental data on the assembly, structure, dynamics and function of a wide range of protein complexes, ranging from small complexes such as haemoglobin 4,5 to large macromolecular machines such as the proteasome [6][7][8] . Furthermore, structurebased protein complex design has become feasible in certain cases [9][10][11][12] . Finally, structural bioinformatic approaches combined with mass spectrometry have revealed that most complexes assemble via ordered pathways that are generally conserved, and that show striking similarities to their evolutionary pathways [13][14][15] .…”
mentioning
confidence: 99%